Regulatory acts for the cultural patrimony preservation of Porto Murtinho, MS, in the context of university network of the Latin american Integration Route (UniRila) and the Bioceanic Corridor - Akamine, Mariana De Barros Casagranda (2021)
This work is part of the activities that were agreed within the scope of the University Network of the Latin American Route (UniRila), and was developed specifically as a proposal for Dossier II. This research is also linked to the development of the Master Plan of Porto Murtinho-MS, specifically the axis of Cultural Historical Heritage, the result of an inter-institutional partnership. In this context, the aim is to analyze current normative acts for the preservation of historical and cultural heritage in the three administrative spheres, using the qualitative approach methodology with bibliographic and documentary research. One of the great challenges of the Bioceanic Route Integration will be the efficient updating of policies for the preservation of the historical and cultural heritage, in order to maintain the cultural integrity of the local population. Thus, it is understood the need to stimulate local development, through cultural and social capital, aiming at a participatory democracy. Heritage education is part of this context as an instrument for disseminating information and knowledge, and when supported by public and private agents and social actors, they are certainly decisive in the struggle arising from issues related to cultural vulnerability.